Geospatial analysis of flood emergency evacuation sites in Accra - Rapheal Ane Atanga; Vitus Tankpa (Jàmbá, 2022)
Cities face frequent flood disasters with devastating impact on lives and property. Geospatial analysis using high elevation points can help to map out emergency evacuation centres for decision making on flood risk management. This research maps and analyses flood emergency evacuation centres in Accra. The objectives of this research were to map out flood hazard and vulnerable settlements, analyse the spatial distribution and identify the optimal locations for flood emergency evacuation sites. The data for this study comprises digital elevation models, stream networks, settlement data, flood risk zone maps of the study site and existing documents on flood disaster risk of the study area. This study adopted the weighted linear combination method to estimate site suitability for emergency evacuation sites. ArcGIS 10.6 was used to analyse the data. The research found that the optimal locations for potential evacuation centres are unevenly distributed between 300 m and 400 m above sea level, most which are in the north-eastern and north-western parts of Accra. The results can contribute to research, policy and decision-making on flood risk management in Accra and other localities with similar conditions. The research further contributes to literature on flood risk management and geographic information system.